Attention Deficit Hyperactivity Disorder (ADHD) and Earnings in Later-Life Self-Employment. (January 2021) - Patel, Pankaj C.; Rietveld, Cornelius A.; Verheul, Ingrid
Recent studies have shown that individuals with attention deficit hyperactivity disorder (ADHD) are relatively often engaged in self-employment. We analyze whether self-employment mediates the relationship between ADHD and earnings. To overcome endogeneity concerns in the estimation of this relationship, we use the polygenic risk score (PRS) for ADHD. In our longitudinal sample of 7, 905 individuals (50–65 years old) from the Health and Retirement Study, a standard deviation increase in the PRS for ADHD increases the odds of self-employment by 32% and decreases yearly earnings by 5%. Self-employment explains (mediates) 59% of the negative relationship between the PRS for ADHD and earnings.